Processo de criação de um corpo: danças com caderno testemunho - Hiche, Gisella Paola Novo (2013)
Process of creation of a body: dances with testimony-notebook is a research that follows through writing the unfoldings of the gesture of dancing and taking notes, which works as a dispositif that in a processual form casts the researcher into another mode of production of subjectivity, whose greatest force is the impersonal of the body activating new practices and thoughts. To keep this dispositif in operation, there is a double effort: that of remaining in retreat regarding what is cultural and socially instituted, and that of simultaneously giving consistence to the creation of a body that will not go towards a form or a concept but will assure the conditions to keep such body undone, alive and open for political, aesthetic e clinical experimentations